Meningkatkan Kemampuan Motorik Halus Anak Melalui Bermain Playdough Alami Pada Kelompok B3 Di TK Ma’had Islam Kota Pekalongan Tahun Ajaran 2020/2021 - Inayatul Millati (AUDIENSI: Jurnal Pendidikan dan Perkembangan Anak, 2022)
This classroom action research aims to improve the fine motor skills of children in group B3 in TK Ma'had Islam, Pekalongan City. This type of research uses classroom action research (CAR). The research subjects were students of the B3 group of TK Ma'had Islam Pekalongan City, totaling 17 children, 12 boys and 5 girls. This action plan goes through 2 cycles, namely cycle I and cycle II. Data collection techniques through observation and documentation. Assessment of the results of the learning process is descriptive percentage to determine the improvement of fine motor skills of children before. The calculation is obtained by comparing the fine motor skills of children before playing natural playdough with the fine motor skills of children after playing natural playdough. If there is an increase in optimal fine motor skills, it means that learning by playing natural playdough has been achieved. The results showed an increase in children's fine motor skills through playing natural playdough in the pre-cycle 30.88.% of 17 children, an increase in fine motor skills in the first cycle of the third meeting 51.74% there was an optimal increase of 20.59% from the initial condition 30.88 % and in the second cycle of the second meeting 87.64%. The application of playdough can improve the motor skills of children in the B3 group at the Ma'had Islam Kindergarten, Pekalongan City